Application of the Main Didactic Principles for Foreign Language Teaching with the Help of the Interdisciplinary Approach - Yuliia Olizko (Pedagogical Discourse, 2015)
An interdisciplinary approach has a big number of different advantages which cause the necessity to apply it in all technical institutions of higher education. The list of recent dissertations of Russian scientists on interdisciplinary integration is provided in the article and general efficiency of application of this approach in foreign language teaching is proved as well. It is found out that teaching based on an interdisciplinary approach opens new opportunities in application of all didactic principles in the English language classes. Implementation of such principles as intersubject coordination, systematic teaching, scientific orientation, presenting teaching matters visible, didactic reduction, securing results, comprehensibility, activity, upbringing, access, individuation and intercultural interaction was studied in the article. Application of these principles were described using the example of teaching students of chemical technology faculty in the National Technical University of Ukraine «Kyiv Politechnic Intitute». In this higher education institution students learn English for 6 years studying these modules: Introduction to English for General Engineering, English for General Engineering, English for Specific Purposes, English for Professional Communication. Business English, English for Specific Purposes (Advanced), English for Scientists 1, English for Scientists 2.